Isovaleric Acidemia as a Rare Cause for Bad Obstetric History - Sailatha Ramanujam (JCDR Research and Publications Private Limited, 2021)
Isovaleric acidemia is an inborn error of metabolism, inherited as an autosomal recessive disorder, caused by deficiency of isovalerylCoenzyme A (CoA) dehydrogenase, leading to elevated plasma isovaleric acid and urine isovalerylglycine levels. Isovaleric acidemia is an unusual disorder with an incidence of 1:67,000 in India. Parents of the child are assumed to be carriers and the offsprings have a one in four (25%) chance of inheriting the disorder. The present article reports a 33-year-old, Gravida 3 Para 2 Live 0 (G3P2L0) at 38 week + 1 day, with previous two Lower Segment Caesarean Surgery (LSCS) and two neonatal deaths, who delivered a term boy baby with incidental finding of isovaleric acidemia at birth. Isovaleric acidemia could sometimes be a rare case for bad obstetric history and should be considered while evaluating a patient. Also, it is now possible to diagnose the condition by early prenatal tests and even before pregnancy by Preimplantation Genetic Diagnosis (PIGD) and by taking necessary steps.